Produksi Kelapa Sawit Provinsi Kalimantan Barat dan Faktor-Faktor yang Mempengaruhinya - Adzani, Rayhan Rizki; Arif, Muhammad (Jurusan Akuntansi Politeknik Negeri Pontianak, 2023)
The palm oil processing industry is one that is believed to be able to help the Indonesian state in increasing per capita income, providing employment, reducing poverty, and as a foreign exchange income. When compared to other vegetable oils like coconut, soybean, or flower oil, palm oil offers advantages sun. This study's goal was to examine the factors impacting the province of West Kalimantan's palm oil production yield between 2015 to 2021. This research uses a scientific techniques and a type of quantitative descriptive research. Secondary sources of data were used in this research. This research's data was obtained between the years of 2015 and 2021 from the websites of the West Kalimantan Province Agricultural Department and the BPS (Central Statistics Administration). In this study, regression with panel data analysis was the analytical technique. The independent factors in this study are land area, labor, and rainfall, while the dependent variable is palm oil production. The outcomes obtained from the panel data regression analysis are land area has a positive effect on oil palm production and rainfall has a positive effect on oil palm production. Meanwhile, labor does not affect palm oil production.